2010
DOI: 10.1002/mnfr.200900476
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic effects of proanthocyanidins and their underlying biochemical and molecular mechanisms

Abstract: Proanthocyanidins are the most abundant polyphenols in human diets. Epidemiological studies strongly suggest that proanthocyanidins protect against cardiovascular diseases. Despite the antioxidant and anti-inflammatory properties of these flavonoids, one of the mechanisms by which proanthocyanidins exert their cardiovascular protection is improving lipid homeostasis. Animal studies demonstrate that proanthocyanidins reduce the plasma levels of atherogenic apolipoprotein B-triglyceride-rich lipoproteins and LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
190
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(200 citation statements)
references
References 152 publications
5
190
0
5
Order By: Relevance
“…Several studies developed in hypercholesterolemic animal models and human subjects have reported a significant reduction in plasma total cholesterol and in lowdensity lipoprotein cholesterol, and an improvement in the endothelial function after supplementation with proanthocyanidins (Tebib et al, 1994;Stein et al, 1999;Bladé et al, 2010). The fact that the present experiment was conducted in normocholesterolemic chicks, and that 21-day-old birds present a lower cholesterol circulating levels than 40-day-old birds (Jin et al, 1998), might contribute to explain the lack of effect on plasma lipids obtained with dietary GSE addition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies developed in hypercholesterolemic animal models and human subjects have reported a significant reduction in plasma total cholesterol and in lowdensity lipoprotein cholesterol, and an improvement in the endothelial function after supplementation with proanthocyanidins (Tebib et al, 1994;Stein et al, 1999;Bladé et al, 2010). The fact that the present experiment was conducted in normocholesterolemic chicks, and that 21-day-old birds present a lower cholesterol circulating levels than 40-day-old birds (Jin et al, 1998), might contribute to explain the lack of effect on plasma lipids obtained with dietary GSE addition.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, gibberellic acid (GA 3 ) and indoleacetic acid (IAA) were chosen because information on their toxicological biological effects in higher animals is very limited. Proanthocyanidin is the most abundant polyphenol in human diets (Blad et al 2010). Recent studies suggest that in vivo grape seeds proanthocyanidin exposure may protect multiple organs from a variety of toxic materials (Yilmaz and Toledo 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The hypolipidemic effect of GSPE may occur through inhibition of VLDL-C secretion by the liver which is mainly due to a reduction in the bioavailability of lipids, mainly TG or the reduction in the availability of free fatty acids to the liver. Another suggestion is the delay and inhibition of dietary fat and cholesterol absorption and a reduction in chylomicron secretion by enterocytes (Blade et al 2010;Shan et al 2010), since GSPE inhibits the absorption of TC and bile acids by decreasing micellar cholesterol solubility. The diminished lipid concentrations by administration of GSPE may be related to the capacity of GSPE to trap reactive oxygen species in aqueous series such as plasma and interstitial fluid of the arterial wall (Yamakoshi et al 1999).…”
Section: Discussionmentioning
confidence: 99%